Deoxygenative Alkylboration of Aldehydes to Synthesize Versatile Secondary α,α-Dialkyl Boronates - Xu, Wenhao; Zhou, Liejin; XU, Tao (Synlett, 2023)
By merging nickel catalysis and photochemistry, we developed a deoxygenative alkylboration of aldehydes via a deoxygenative difunctionalization of carbonyls strategy. This three-component reaction between alkyl halides, B2Pin2, and aldehydes represents one of the most efficient methods to furnish the versatile secondary α,α-dialkyl boronates. A series of deoxygenative difunctionalization skeletons can be gained from the products based on the carbon–boron bond transformation. In addition, deoxygenative arylboration of aldehydes was achieved.
Keywords: deoxygenative difunctionalization of carbonyls; C–O bond coupling; metallaphotoredox; nickel; cross-coupling